Cosmological redshift and Hubble tension explained by means of the FLRWT time-metric framework and transit physics in the IGM - Trinchera, Alessandro (Frontiers in Astronomy and Space Sciences, 2023)
In response to all current cosmological controversies, this paper provides a reliable explanation to the Hubble tension as well as to the apparent acceleration of space expansion detected by SN Ia. In the first place, it calculates the redshift from Einstein field equations (EFE) assuming a Friedman-Lemaitre-Robertson-Walker-Trinchera (FLRWT) metric framework due to the deformation of the spacetime fabric, causing a redshift due to a time dilation. In the second place, this study computes the dominant cosmological redshift contribution given by the transit redshift due to multiple interactions photons-electrons in the intergalactic medium and not sustained in EFE. It is fully consistent with Wigner’s Solid-State Physics and Ashmore’s Physics which predict the crystallization of free electrons at very low temperatures and the interaction with photons of light without scattering and blurring effects. The outcome of this inquiry fully matches the observational data given by the redshift-independent extragalactic distances (NED-D) and by the Chandra/XMM-Newton database of quasars for a specific density of matter in the Universe.